Parts Without a Whole: Mourning, Redemption and Desire in Partes de África. - SAADE, SEBASTIÁN PATRÓN (Bulletin of Hispanic Studies (1475-3839), 2014)
In this article, I argue that Partes de África, by Hélder Macedo, questions our ideas about the outcome of history. The novel distances itself from the long-ingrained belief in a redeeming future, since the future, contrary to what is believed, is already traced and designed. In marked contrast to the future, the past retains all of its possibilities intact. The homogeneous historical narrative that cancels difference and imposes a single, inevitable history, is recognized as what it is by Partes de África: a fiction made up of shattered pieces scooped from a bigger sample. Time's fragmentation is required to preserve difference between the pieces that compose the last years of Portuguese imperialism, as well as to preserve the difference between cultures. The acknowledgement of difference is an imperative of the structure of Partes de África, since fragmentation - even if it comes through the work of mourning - is the only possibility the author-narrator has of redeeming the memory of his father.